Alcalde versus friar in Camarines - Mallari, Francisco (Philippine Studies, 1992)
Nineteenth-century Libmanan, a town of Camarines Sur, was situated on flat terrain on the left bank of the Bicol river, about a league (3.46 miles) from San Miguel bay. It was once a visita of Quipayo till 1586 (de Huerta 1865, 193). On assuming the status of a town, it took control over an extensive territory . Its jurisdiction stretched from the coast of San Miguel Bay to the shores of Ragay gulf and from the boundaries of Sipocot to those of Maragao and Canaman towns. Its sprawling territory was a boon to its inhabitants and probably a factor in their lighthearted, lovable, liberal and hospitable to a fault, so much so that their fiestas attracted many, and their customs and culture distinguished them from other Bicolanos (Ruiz 1887,fols 219-20). At times, however, Libmanan's broad expanse was also a source of woe. Til the nineteenth, its exposed borders were very vulnerable to Moro attacks . its defenses were weak, and its population so widely dispersed that mustering organized resistance against hostile invasions was frustrating. All too often, Moro marauders landed with impunity on the northern coast and on the southern coast between Ragay and Pasacao, and invaded the town-proper.